Análise das estratégias do projeto para incorporação de princípios e indicadores de sustentabilidade em políticas públicas no município de Jaboticabal-SP - Adeodato, Marise Tissyana Parente Carneiro (2005)
Recent debates about urban development have introduced sustainability as an important principle to consider solutions to socioenvironnmental problems. In the other hand, changes on traditional concepts of urban management have included social participation and democracy on decision processes. In this context, instruments like social, environmental and sustainability indicators have helped to support and monitor public policies toward new perspectives of more sustainable development of the cities, in its environmental, economical, social, cultural and political dimensions. To make it possible, it is necessary to verify such possibilities as limitations in this attempt of incorporate sustainable principles on urban policies. The main objective of this research is exactly to analyze conditions that allow monitor sustainability of public policies by indicators, basing on the case of the Sustainable Jaboticabal Project, an experience developed in Jaboticabal (SP) city, in its first and second phases (1999-2004). As categories of analysis of the process, have been chosen strategies and actors, represented by civil society, public management and researchers. To obtain the results of this research were used even quantitative and qualitative data sources, supported by interviews and organized informations of the Project. The results reveal as favorable conditions to monitor sustainability in public policies: integral education of people about principles, dimensions and indicators of sustainability; social mobilization organized and emancipated to participate of processes for more sustainable urban policies; support of technician-politics assessors to facilitate the learning and intermediate relations between actors; the sponsorship of public managers to processes of innovation toward a participatory and sustainable urban management.